Superalloys 718, 625, 706 and Various Derivatives (2005) 2005
DOI: 10.7449/2005/superalloys_2005_97_110
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Life of DA718 for Aircraft Engine Disks

Abstract: The micro-mechanisms of crack initiation and propagation identified for DA 718, as well as the competition between initiation site types and locations, cannot be accurately accounted for by current certified methods used to establish aircraft engine disks life,essentially phenomenological.Once identified, these micro-mechanisms have been modelized by mesoscopic models using very few parameters and depending strongly on material mechanical behavior. LCF data scatter was mainly attributed to probabilistic nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It should be added that in many cases it has been observed that the fatigue cracks can be initiated at bulge-like features formed by volume expansion of oxidising NbTi (CN) particles [154,155]. It is easily understood that this situation implies a size effect: the fatigue life is a decreasing function of component size as shown by Deyber et al [156].…”
Section: Microstructural Degradation Due To Surface Oxidationmentioning
confidence: 96%
“…It should be added that in many cases it has been observed that the fatigue cracks can be initiated at bulge-like features formed by volume expansion of oxidising NbTi (CN) particles [154,155]. It is easily understood that this situation implies a size effect: the fatigue life is a decreasing function of component size as shown by Deyber et al [156].…”
Section: Microstructural Degradation Due To Surface Oxidationmentioning
confidence: 96%
“…Furthermore, fine grain microstructures (ASTM > 10) were demonstrated to be particularly sensitive to crack initiation when brittle surface or near-surface NMIs were present, especially at low temperatures [1,[4][5][6][7][8][9][10][11]. While NMIs in fine grain IN718 alloys are important in this cycling regime, other microstructural features such as coarse favorably oriented grains or twin boundaries can also play a key role in the crack initiation process [12][13][14][15]. At lower cyclic stress amplitudes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, crack initiation due to carbide or carbonitride are widely reported [9,11], and especially for fatigue tests on 718 Alloys.…”
Section: Discussionmentioning
confidence: 99%